Weakly acidic microenvironment of the wound bed boosting the efficacy of acidic fibroblast growth factor to promote skin regeneration - Pan, Qiao; Fan, Ruyi; Chen, Rui; Yuan, Jiayi; Chen, Shixuan; Cheng, Biao (Frontiers in Bioengineering and Biotechnology, 2023)
The pH value within the wound microenvironment influences indirectly and directly all biochemical reactions taking place in the process of skin wound healing. Currently, it is generally believed that a low pH value, such as it is found on normal skin, is favorable for wound regeneration, while some investigations have shown that in fact alkaline microenvironments are required for some healing processes. The role of growth factors in promoting wound healing requires a specific microenvironment. In wound microenvironments of different pH, growth factors with different isoelectric points may have different effects. To explore whether the application of FGF with different isoelectric points in wounds with different pH values interferes with the healing process to different degrees, GelMA hydrogels with different pH values were prepared to maintain the wounds microenvironment with the same pH values, in which aFGF and bFGF were loaded as well. The results show that GelMA hydrogels of different pH values maintained the same pH of the wound microenvironment sustainably on the 4th day. Moreover, aFGF and bFGF promoted skin wound healing to varying degrees in different pH wound microenvironments. In particular, aFGF significantly promoted wound re-epithelialization in a weak acidic microenvironment, while bFGF promoted collagen synthesis and deposition in the early stage of weak acid wounds. In addition, aFGF plays a superior role in inhibiting inflammation in weak acidic wounds.